New Technology of Soil Preparation for Planting Police Crops (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2023)
The article describes the new technology of soil cultivation and its preparation, which provides for the joint implementation of such technological processes as tillage with and without a tiller, loosening the sub-layer along the seeding line and local application of fertilizers, preparing the soil for planting and opening an irrigation ditch. The structure, working principle and field test results of the combined unit implementing the new technology are presented.